Comprehensive Immunological, Hematological, and Inflammatory Profiling in Active COVID-19, Convalescent, and Healthy Control Populations - Majed Kadhium, Noora (Medical Science Journal for Advance Research, 2026)
Background: COVID-19 expressed with different clinical severity come from impaired regulated immune responses. Aim of the study: The present study was aimed to completely compare between hematological factors, SARS-CoV-2-specific responses of antibodies, and inflammatory cytokine description among three distinct cohorts: active COVID-19 infected patients, healed individuals, and healthy controls which were unexposed to virus. Methods: descriptive study included 450 participants (150 for every group). Active patients were RT-PCR supported; healed individuals which were ≥4 weeks after symptom resolution; healthy controls which had no previous viral infection or vaccination. Blood samples have been tested for SARS-CoV-2 antibodies (anti-spike IgG, neutralizing antibodies, anti-nucleocapsid IgG), complete blood counts, and cytokines (IL-6, TNF-α, IFN-γ) were done via multiplex immunoassay. Result: The present study yield a full detailed comparative- based analysis of main biomarkers among 450 individuals classified into active SARS-CoV-2 infection (n=150), recovered individuals (n=150), and healthy controls (n=150). the present study assess SARS-CoV-2-specific antibodies (nucleocapsid IgG, spike IgG, neutralizing antibodies), hematological factors, and inflammatory cytokines (TNF-α, IL-6, IFN-γ). Clinicall active infection was described by considerably increased antibody responses, lymphopenia, neutrophilia and a significant pro-inflammatory cytokine analysis with high IL-6 (268.4±44 pg/mL) and TNF-α (218.6±39.3 pg/mL). on the other hand, IFN-γ mesures were maximum in recovered individuals (117.5±5.8 pg/mL), indicating a shift toward antigen specific immunity. These results outlined unique immunological stages of COVID-19 and have effects for comprehension of the pathogenesis, treatment targeting, and prolonged immunity Conclusions: Active COVID-19 is defined by over activated antibody mediated immunity, pro-inflammatory cytokine control (IL-6/TNF-α), and hematological abnormal regulation. Recovery includes shift into regulated immunity with persistent neutralizing antibodies and high IFN-γ, indicating establishment of immunological cellular memory. These different immunological signatures among infection phases might inform prognostic assessment and stage-specific therapeutic strategies.